2017
DOI: 10.5603/ep.a2017.0032
|View full text |Cite
|
Sign up to set email alerts
|

The age of developing diabetes and FTO polymorphisms (rs9939609, rs1421085, and rs9930506)

Abstract: Introduction: Type 2 diabetes (T2DM) is a common complex metabolic disorder that has a strong genetic predisposition. Fat mass and obesity-associated protein (FTO) is one of the genes of interest to us. Hypomethylation of a CpG site in the FTO gene was significantly associated with the risk of T2DM. The aim of the study was to find the answer to the question of whether the polymorphism changes of the FTO gene in the pathogenesis of type 2 diabetes are comparable in young, middle aged, and elderly people. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…FTO located on 16q12.2 is substantially associated with elevated basal metabolic rate and T2DM [ 46 ]. Numerous FTO gene variants have been reported with an amplified contributory effect on T2DM and obesity [ 47 , 48 ]. However, our study showed that SNP rs1164284 had the most substantial susceptibility to prediabetes in the Arab population.…”
Section: Discussionmentioning
confidence: 99%
“…FTO located on 16q12.2 is substantially associated with elevated basal metabolic rate and T2DM [ 46 ]. Numerous FTO gene variants have been reported with an amplified contributory effect on T2DM and obesity [ 47 , 48 ]. However, our study showed that SNP rs1164284 had the most substantial susceptibility to prediabetes in the Arab population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a significant association between FTO rs11642841 (correlated with FTO rs9939609) and total sugar intake was reported [ 57 ]. A potential mechanism related to the interaction of these four particular FTO SNPs with SSBs may be explained by their association to sugar metabolism and insulin resistance [ 58 , 59 ], although reports on the role of rs1421085 in glucose metabolism were inconclusive [ 60 , 61 ]. Our results reinforce previous findings, but more importantly, they complete a bigger picture of a potential intervention strategy to prevent the effect of SSB consumption by targeting guidelines in this genetic group predisposed to obesity, specifically in women.…”
Section: Discussionmentioning
confidence: 99%